4,4′-Dimethoxy-2,2′-[methylazanediylbis(methylene)]diphenol - Chatchai Veranitisagul (Acta Crystallographica Section E, 2012)
The title compound, C17H21NO4, shows an intramolecular hydrogen bond between a phenol OH group and the N atom. In the crystal, molecules are connected by pairs of O—H...O hydrogen bonds into inversion dimers.